New Formats of U.S. Nuclear Alliances and Their Impact on the Treaty on the Non-Proliferation of Nuclear Weapons - R. A. Ustinov (Сравнительная политика, 2024)
This article examines the impact of new formats of nuclear cooperation launched by the United States with its allies on the international nonproliferation regime established by the Treaty on the Non-Proliferation of Nuclear Weapons (NPT). The two examples of such cooperation outlined in this article are the AUKUS partnership between Australia, United Kingdom and Untitled States that involves transfer to Canberra of a large amount of highly-enriched uranium for use in nuclear-powered submarines, as well as the extended deterrence between the United States and the Republic of Korea. This material presents the analysis of how (if at all) these initiatives are compatible with the NPT and what the most problematic elements are in each case in relation to the Treaty and its regime. It derives from the research that has been conducted that the new formats of United States’ nuclear cooperation are undermining the NPT regime and its international standing. As a result of such cooperation the NPT loses its unique international legal core that for more than half a century has allowed to stop proliferation of nuclear weapons. The norms that lied in the basis of the Treaty are also being eroded. Such tendencies create a completely new environment and inevitably affect security calculus of other States Parties to the NPT. Against this backdrop further decrease of the political weight of the Treaty cannot be excluded, together with its role in upholding international peace and stability. Such transformations may require a brand new look at and approach to the international nonproliferation regime in the future.